Rancang Bangun Alat Pemberi Pakan Ikan Konsumsi Otomatis Berbasis Mikrokontroler - Satriyo Cahya Rachmanda; aprilianto, tria (JURNAL SISTEM KOMPUTER ASIA, 2023)
Feeding fish is one of the important things in cultivating fish. Currently feeding is generally still dependent on human resources that are manual. Therefore designed tools to feed fish that can work automatically based on the time or schedule of feeding fish. The Automatic fish feeding tool consists of several interconnected hardware that is NodeMCU ESP8266 as controller, ultrasonic HC-sr04 sensors to detect the availability of fish feed, Servo Motor for feed production through valves That can control, DC motors are controlled by the relay module for the spin-off fan. Based on the results of analysis and testing that has been done the conclusion that the automatic fish feeding system in this research can work optimally. This tool can access automatic fish feeding system that use the application so that it can control the scheduling through the application on Android and can know the availability of fish feed in the container listed in the application.